Analysis of Nursing Care in Mr. M with Hypertension and the Application of Benson Relaxation Therapy - Riswandi, Aditya; Wahyudin; Sugih Permana, Gin Gin (CV. Literasi Publikasi Indonesia, 2024)
Age-related changes in the cardiovascular system are one of the leading causes of various health problems among the elderly, particularly hypertension. Hypertension is a major risk factor for several cardiovascular diseases, including coronary heart disease, heart failure, pulmonary heart disease, cardiomyopathy, stroke, and kidney failure. Non-pharmacological treatments, such as Benson's Relaxation Therapy, have shown promise in managing hypertension by reducing blood pressure through relaxation techniques. This case study aims to explore the application of Benson's Relaxation Therapy as an intervention for hypertension in elderly patients with cardiovascular disturbances. The purpose of this case study is to provide an overview of the implementation of Benson's Relaxation Therapy as an intervention for hypertension and its impact on cardiovascular health in elderly patients. A descriptive case study design was used, which included anamnesis, observation, physical examination, and medical records review. The nursing care process was based on evidence-based practice (EBP) principles. The case involved a patient diagnosed with hypertension who was treated with Benson's Relaxation Therapy. The nursing interventions were analyzed in relation to hypertension management and its effects on the cardiovascular system. The study found that the patient presented with nursing diagnoses including acute pain, impaired physical mobility, and fall risk, with the primary issue being acute pain caused by elevated blood pressure. Benson's Relaxation Therapy was applied and led to a reduction in blood pressure over three therapy sessions. This empirical evidence suggests that Benson's Relaxation Therapy is an effective intervention for managing acute pain associated with elevated blood pressure in hypertensive patients. Therefore, it can be concluded that Benson's Relaxation Therapy is effective in lowering blood pressure in hypertensive patients in the Dahlia Room of Griya Lansia, Garut Regency. The application of Benson's Relaxation Therapy has proven to be effective in reducing blood pressure in hypertensive patients in the Dahlia Room of Griya Lansia, Garut Regency, Indonesia.